Can a probiotic supplement in pregnancy result in transfer to the neonatal gut: A systematic review. (30th May 2020) - Moore, Rebecca L.; Geraghty, Aisling A.; Feehily, Conor; Saldova, Radka; Murphy, Eileen F.; Van Sinderen, Douwe; Cotter, Paul D.; McAuliffe, Fionnuala M.
Abstract: Introduction: The establishment of the neonatal gut microbiome is a crucial step that may have lifelong health implications. We aimed to systematically review evidence on maternal probiotic supplementation during pregnancy and vertical transfer of the corresponding strain to the infant gut. Material and methods: Medline, CINAHL, Embase, Web of Science, and OVID were searched from inception to September 2018. Studies of maternal probiotic supplementation for a minimum duration of 2 weeks and analyses of neonatal stool samples were included. The primary outcome was presence of the specific probiotic strain in the infant stool. Electronic databases were searched for relevant studies and references were cross‐checked. Risk of bias among included studies was assessed and data were extracted independently by two authors. Results: Three studies were included in the review. Only one study was identified involving prenatal maternal probiotic supplementation alone. Neonatal colonization with the maternally administered probiotic was not demonstrated but supplementation with the probiotic influenced levels of a bacterial strain other than that found in the probiotic product. The other two studies identified included both prenatal and postnatal supplementation of either mother or infant. All three studies reported employing strain‐specific isolation methodology to isolate the supplemented bacterial strain in infant stool but none used whole metagenome shotgun sequencing. Conclusions: Few studies investigating transfer of a specific probiotic bacterial strain from mother to infant were identified, showing inconclusive evidence of vertical transfer.